Supporting Community Health Workers After a Disaster: Findings From a Mixed-Methods Pilot Evaluation Study of a Psychoeducational Intervention. (28th June 2016) - Powell, Tara; Yuma-Guerrero, Paula
Abstract: Objective: Community health workers (CHWs) in disaster-affected areas are at risk for emotional distress, as they support others while they may be in the process of rebuilding their own lives. The Resilience and Coping for the Healthcare Community (RCHC) intervention was developed in response to the stress CHWs faced after Hurricane Sandy. The intervention uses psychoeducation to help participants identify common stress responses, recognize signs of job burnout, and utilize healthy coping strategies. Methods: A mixed-methods pilot of the RCHC intervention was conducted in 2013 with a convenience sample of staff from 6 federally qualified health centers (n=69). Validated measures of stress, coping, compassion fatigue and satisfaction, burnout, stress, and social provisions and a measure of perceived knowledge were administered at baseline, after the workshop, and at a 3-week follow-up. Semi-structured interviews were conducted with 10 randomly selected participants and were analyzed by using content analysis. Results: From baseline to the post-workshop assessment, perceived knowledge scores increased from 24.59 to 30.34, t (62)=5.16 ( P <0.001), and acute stress scores decreased significantly from 10.53 to 6.78, t (64)=4.74 ( P <0.001). Significant increases from baseline to the 3-week follow-up (n=45) were found for perceived knowledge (24.05 to 27.24; t (40)=5.37; P <0.001), and social provisions (27.34 to 28.39; t (44)=2.15; P <0.05). Conclusions: Our qualitative findings indicated that the respondents valued learning about common stress responses and incorporating coping as part of a daily routine. Team building and normalization of emotions were seen as ancillary benefits that would reduce stress levels in the workplace. In conclusion, the RCHC intervention shows promise and should be investigated further in experimental studies. ( Disaster Med Public Health Preparedness . 2016;page 1 of 8)